2001
DOI: 10.1007/s004360000326
|View full text |Cite
|
Sign up to set email alerts
|

Novel small strongyle (Cyathostominae) beta-tubulin sequences

Abstract: Several coding sequences of the benzimidazole (BZ) target beta-tubulin have been described for different parasitic nematodes. However, until recently no tubulin sequences from Cyathostome species were available, despite the importance of BZ resistance in horses in the field. Here, we describe several full-length beta-tubulin coding sequences of two major small strongyle species, namely Cylicocyclus nassatus and Cyathostomum coronatum. In the latter sequence, the putative BZ resistant mutation in codon 200 lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 11 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…Unlike the large strongyle (Strongylinae) group, anthelmintic resistance is common in the Cyathostominae, particularly with regard to benzimidazole compounds such as fenbendazole [54]. Most horses harbour burdens of tens of thousands of these parasites without developing clinical disease, but in some horses, cyathostomin infection leads to a severe inflammatory enteropathy affecting the large intestine [18,32].…”
Section: Background To the Cyathostominaementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the large strongyle (Strongylinae) group, anthelmintic resistance is common in the Cyathostominae, particularly with regard to benzimidazole compounds such as fenbendazole [54]. Most horses harbour burdens of tens of thousands of these parasites without developing clinical disease, but in some horses, cyathostomin infection leads to a severe inflammatory enteropathy affecting the large intestine [18,32].…”
Section: Background To the Cyathostominaementioning
confidence: 99%
“…The sequence of β-tubulin isotype I gene has been described for seven common cyathostomin species [43,54]. One report suggested that the mutation at codon 200, which is associated with BZ resistance in ruminant nematodes, may not be responsible for BZ resistance in cyathostomins [55].…”
Section: Cyathostomin Anthelmintic Resistancementioning
confidence: 99%
“…Variation in b-tubulin amino acid sequences among the currently sequenced genes of different nematode species is low with similarities of around 90% (Bennett et al 1999;Pape et al 1999;Brehm et al 2000;Samson-Himmelstjerna et al 2001). Variations in nucleotide sequences are more marked.…”
Section: Introductionmentioning
confidence: 94%
“…Two alleles of the β-tubulin isotype 1 gene from Cylicocyclus nassatus, representing the wild type and the F200Y polymorphism, were isolated and inserted into a cloning vector as previously reported (von Samson-Himmelstjerna et al 2001). The third allele with the F167Y polymorphism was subsequently processed in the same manner.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…The genotyping of BZ-resistant populations by allele-specific PCR failed to find a correspondingly high frequency of the TAC polymorphism (von Samson-Himmelstjerna et al 2001). Despite an increase in the frequency of the TAC polymorphism during the development of resistance, another study that monitored TTC/TAC allele frequencies concluded that other mechanisms may be involved in the development of BZ resistance in cyathostomins (Pape et al 2003).…”
mentioning
confidence: 99%